Analysis of the Drapeability and Bending Rigidity of Clothing Packages—A Preliminary Study - Michał Stępień; Iwona Frydrych (Textiles, 2025)
This paper concerns the study of the multidirectional drape and bending rigidity of clothing packages combined with three types of adhesive inserts. The aim of this research was to investigate the effect of introducing seams of differentiated complexity to clothing packages consisting of cotton fabric and adhesive inserts. The adhesive inserts were differentiated according to their mass per square meter. Three kinds of seams differing by the number of bent and sewn layers were introduced into packages, and two techniques of bonding, differentiated by the sequence of operations, were applied. The results of the influence of bonding technique on the bending rigidity and multidirectional drape for packages with seams and those without them are discussed. All of the tests carried out were aimed at answering the question of how seam introduction and its complexity (the number of sewn layers) influence the bending rigidity and drapeability of clothing packages in order to facilitate clothing technologists in the proper selection of appropriate adhesive inserts for the engineered design of clothing products.